An Overview on Interdisciplinary Curriculum in Higher Education - Hedayat-Ollah Etemadizadeh; Ahmadreza Nasr; Mohamadjavad Liaghatdar (Interdisciplinary Studies in the Humanities, 2009)
Interdisciplinarity, interdisciplinary education and interdisciplinary curricula are increasingly used in Higher Education field. These terms are used with or interchangeably with similar terms such as multi-disciplinarity, pluridisciplinarity crossdisciplinarity and transdisciplinarity. Although interdisciplinary approach to curriculum lost its significance in last decades and disciplinary approached was focused for about two decades, but the ideas of interdisciplinary and integrated curricula are not new ones and are rooted in the thoughts of the previous scholars who were famous for their concerns about unity of knowledge, forming coherence, general and all-inclusive knowledge. In this paper while offering theoric and historical views on interdaisciplinarity, interdisciplinary approach to curriculum, academic disciplines, a variety of possible combinations of disciplines across curricula, a sociological criticism about disciplinary curriculum, a biological explanation for interdisciplinary curriculum, models, strategies, advantages, and pitfalls of interdisciplinary curriculum are discussed.